PENGARUH PESTISIDA NABATI BUAH CABAI (Capsicum annuum L) DAN UMBI BAWANG PUTIH (Allium sativum L) TERHADAP MORTALITAS HAMA BAWANG MERAH (Spodoptera exigua Hubner) - Nursam Nursam; Mohammad Yunus; Burhanuddin Nasir (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
Shallot (Allium cepa) is one type of horticultural commodities that have great opportunities in the agribusiness sector. However, the shallot cultivation has still been facing with beet armyworm (Spodopter exigua) pests.  The purpose of this study was to determine the effect of botanical pesticide made from chilli (C. annuum) and garlic (A. sativum) on mortality of larvae of S. exigua. The research was carried on in the Laboratory of Plant Pests, Faculty of Agriculture, University of Tadulako from September to December 2015. This study used a completely randomized design (CRD) with seven treatments, each treatment was repeated three times so there were 21 experimental units. The composition of the treatmentswas as follows: control (p0, water only), 2 ml fresh chilli/100 ml water (p1), 4 ml rotten chilli/100 ml water (p2), 6 ml fresh garlic/100 ml water (p3), 8 ml rotten garlic/100 ml water (p4), 10 ml rotten chilli + rotten garlic/100 ml water (p5), 12 ml fresh chilli + fresh garlic/100 ml water (p6). The results showed that the concentration of 10 ml of rottenchilli + rottten garlic/100 ml water is very effective in suppressing the S. exigua larvae by 83% – 96% within 3 – 4 days after the botanical pest application.Keywords: Botanical pesticides, Mortality of Spodoptera exigua Hubner.